DISCOVERY OF WHITLOCKITE IN MANTLE XENOLITHS: INFERENCES FOR WATER- AND HALOGEN-POOR FLUIDS AND TRACE ELEMENT RESIDENCE IN THE TERRESTRIAL UPPER MANTLE - Ionov D.A.; Hofmann A.W.; Gurenko A.A.; Hellebrand E.; Merlet C.; Montagnac G.; Gillet P.; Prikhodko V.S. (My University, 2006)
Chemical analyses and Raman micro-spectroscopy have identified whitlockite (water- and halogen-free phosphate) in mantle xenoliths from Siberia. Whitlockite has not previously been reported from terrestrial mantle-derived rocks, but is the most common accessory phosphate in meteorites and igneous rocks from Mars and the Moon. The presence of the 'anhydrous' whitlockite, together with the breakdown of 'hydrous' accessory minerals (amphibole, phlogopite) in the same xenoliths, indicates that portions of the terrestrial upper mantle may be nearly as low in water and halogens as in inner parts of the smaller solar system bodies, regardless of enrichments of other highly mobile components (phosphorus, alkalis). Whitlockite may be an important host for some lithophile trace elements in those portions of the terrestrial mantle. It contains up to 3 times more rare earth elements than coexisting apatite but less Sr, Ba and U while Th abundances are similar. Thus, trace element abundances, patterns and ratios (e.g. Sr/Nd, Th/U) in whitlockite-bearing mantle rocks and coexisting fluids may be distinct from those for mantle rocks containing only apatite and/or other 'hydrous' minerals. Several generations of both whitlockite and apatite with different textural positions and abundances of Na, Mg, Sr and LREE were identified in some of the xenoliths. Furthermore, precipitation of the phosphates was accompanied by the formation of a distinct generation of clinopyroxene, which contains much less Zr (up to 10 times) but more LREE than clinopyroxenes formed in previous metasomatic episodes. © 2006 Elsevier B.V. All rights reserved.
Keywords: APATITE; METASOMATISM; TERRESTRIAL MANTLE; TRACE ELEMENTS; VOLATILES; WHITLOCKITE